Tribology of polymer composites : characterization, properties, and applications - Rangappa, Sanjay Mavinkere; Siengchin, Suchart; Parameswaranpillai, Jyotishkumar; Friedrich, Klaus, 1945- (Elsevier, 2020)
Tribology of Polymer Composites: Characterization, Properties, and Applications provides an exhaustive overview of the latest research, trends, applications and future directions of the tribology of polymer composites. Covering novel methods for the synthesis of polymer composites and their properties, the book starts by reviewing the fabrication techniques, wear and frictional properties of polymer composite materials. From there, it features chapters looking at the tribological behavior and properties of specific polymer composite materials such as synthetic fiber-reinforced, cellulose fiber-reinforced, wood fiber, synthetic fiber, mineral fiber-reinforced, and thermosetting composites. Final chapters cover the tribology of polymer nanocomposites and particulate polymer composites and their metal coatings. Applied examples spanning a wide range of industries are emphasized in each chapter.
Outline to tribology of polymer composites Recent advances in tribology of hybrid polymer composites Development and tribological properties of polymer composites Tribological behavior of fiber-reinforced polymer composites Tribological characterization of cellulose fiber-reinforced polymer composites Effect of adding sisal fiber on the sliding wear behavior of the coconut sheath fiber-reinforced composite Influence of coconut and graphite fillers on the wear and friction behavior of epoxy composites Tribological behavior of nanoclay-filled basalt fiber-reinforced polymer composites Slurry jet erosion wear of particulate polymer composites and metal coating Tribology of thermosetting composites Tribological studies of surface-modified sansevieria cylindrica fiber-reinforced polyester composites Friction and wear properties of carbon nanotube-reinforced polymer composites Sustainable tribology: Processing and characterization of multiscale thermoplastic composites within hydropower applications Tribological characterization of different mesh-sized natural barite-based copper-free brake friction composites Tribological studies and modal analysis on biocomposite/PVC core sandwich panels Synergism of fillers on adhesive and abrasive wear of thermoplastic copolyester elastomer composites Tribological applications of polymer composites
Keywords: Polymeric composites.; Tribology.; elektronické knihy; electronic books